Study of QR Code Technology Application for Monitoring Activity of Ship Planned Maintenance System - Sufian Imam Wahidi; Triwilaswandio Wuruk Pribadi; Hajid Mulya Rahman (Department of Naval Architecture - Diponegoro University, 2022)
System and outfitting in a ship vary with different brands and treatment methods. These conditionscan be an issue if the operator has undisclosed damages due to a lack of knowledge about the ship'smaintenance records. An electronic planned maintenance system (ePMS) is a system that is currentlyused to collect the ship maintenance recorded data. However, the use of ePMS still has drawbacks. Theappearance is less interactive, available information about the outfitting used in ships is limited, andthe operator needs to search the outfitting manually with scrolling. This research aims to study theapplication of QR code technology for monitoring maintenance activities of ship systems and outfitting.This research was conducted based on field observation of ePMS, designing a QR code module for theePMS application, developing algorithms, and creating programs for website and android basedapplications. In addition, trials of the application and calculation of the costs incurred for implementingthe QR code method are also carried out. The distribution of questionnaires for practitionersaccompanied the trial. Based on that, the implementation of QR code in ePMS can be applied, easy touse and facilitate the supervision of ship system and outfitting activities with a mean score of 4.39 orequivalent to strongly agree. The addition of the QR code module is costed IDR120,426,000.00, wherethe process of recognizing and searching for ship systems and outfitting to view maintenance plansand maintenance history on the ePMS application is enough by scanning a QR code.